Konsep Earned Value dalam Aplikasi Pengelolaan Proyek Konstruksi - Priyo, Mandiyo; Wibowo, Noor Adi (Semesta Teknika, 2008)
Earned value concept is one of monitoring technique on construction process which is based on the integrated concept of cost and time. Using integrity of time and performance of field works, earned value method can accommodate the need of performance monitoring of construction project. The aim of this research is to observe the suitability of construction cost and time in the report compared to the plan report. In this research, observed data were taken from the bridge replacement project. The results show that the project construction at the end of 4th, 8th and 12th week with positive value of schedule variances, SV = 2.20 week, 0.4606 week and 0.9963 week, respectively, present the construction process is faster than schedule. While, positive value of cost variances, CV = IDR 3,543,762.17, IDR 115,583,274.67 and IDR 206,090,828.00 at the end of 4th, 8th and 12th weekÂ shows that the cost of construction project is lower than budget plan. However, evaluation at the end of 16th week shows that the SV value is -0.1946 which means that the construction works are delayed from the schedule. Based on its CV value of IDR 196,892,110.00, the cost project is lower than the budget. These results are supported with the performance index of SPI which is lower than 1 and CPI is higher than 1.Â Â